Reflection on pastoral care in Africa: Towards discerning emerging pragmatic pastoral ministerial responses - Vhumani Magezi (In die Skriflig, 2016)
Pastoral care takes different forms in responding to people’s needs in their context. Accordingly, over the centuries it has evolved in response to emerging needs. Historical developments in pastoral care are well-documented. However, pastoral care in Africa has a short and unsystematically documented history. Scholarly discussions on pastoral care concerning the continent tend to be considered under African theological frameworks. Notwithstanding the already existing weaknesses in African theological discussion, pastoral care in Africa has remained fragmented with diverse and seemingly knee-jerk approaches in guiding individuals who provide pastoral care. In view of this, this article firstly aims to provide a broad overview and initiate a discussion on the current challenges in pastoral care in Africa. Secondly, it aims to reveal some gaps worth pursuing by scholars in the discipline. Thirdly, it sheds some light on approaches employed by pastoral practitioners in pastoral ministry practice. In doing so, this article opens the lid on some perspectives adopted in ministry work on the frontlines, that is, providing pastoral care to people in their communities – particularly church communities. This article first outlines the problem to be addressed followed by an overview of pastoral care in Africa. It then proceeds to address potential research opportunities within the discipline. Finally, it highlights some emerging approaches in providing pastoral care in the communities. This article does not focus on one particular pastoral care issue, but gives an overview of the situation relative to pastoral care in Africa and the emerging responses.